Practical Use of Soybean Meal and its Supplementation With Amino Acids in Diet of Mystus Nemurvs (Cuvier and Valenciennes) Fingerlings - Md. Asaduzzaman (2000)
Two experiments using different formulation of diets to determine the suitability of soybean meal in diet for Mystus nemurus fingerlings were carried out. In the first experiment, seven types of formulated diets were used to evaluate the effect of partial or complete replacement of fishmeal (FM) with solvent-extracted soybean meal (SSBM) and full-fat soybean meal (FFSBM) for the river catfish, Mystus nemurus fingerlings. Six isonitrogenous diets (42% crude protein) containing different content of FM:SSBM were D1(61.29:0.0%), D2(39.78:30%), D3(32 .6:40%), D4(25 .44:5 0%), Ds(18.37:60%), and D6(O.O:85.84%) were randomly fed to catfish in triplicate tanks. The seventh diet (30% crude protein) containing 0% FM and 85.42% FFSBM was also used in the same manner. Average individual weight gain, feed conversion ratio, specific growth rate, protein efficiency ratio, and yield were not differ significantly (p>0.05) among the two comparable diets CDI and D4) where the FM and SSBM percentage were 6 1 .29, 2 5 .44 and 0, 50%, respectively. But apparent net protein utilization (between DJ and D4) was d iffering significantly (p<0.05). Survivability of the fish fed diet DJ and diet D4 with the value of 8 1 .90 and 80.95%, respectively. Th is study indicate that 5 8.49% FM can be replaced by S SBM i n the diets for better growth for intensive culture. In the second experiment, seven types of isonitrogenous (42% protein) diets having fish meal with soybean meal (Control diet) and different proportion of soybean meal supplemented with three selected ind ispensable crystalline amino acids were used to determ ine their suitability as feed for Mystus nemurus fingerlings under close water recirculating system . Casein was added to make up 42% protein. The study showed that M nemurus fed the control diet CD) with 25.44% FM and 50% S SB M (same as in experiment 1) had highest growth performances. The species fed the diet with 57% SSBM (D3) with the selected amino acids had the second highest growth performances. But between the two treatments CD) and D3) had no significant differences (P>0.05) on the basi s of weight gain (%), FeR, SGR, PER, yield and surv ival. Amino acid profiles of whole-body M nemurus fingerlings at different feed ing trials were determined to provide baseline information on the amino acid requirements of the fresh water catfish. The essential am ino acid (AlE) ratio were calculated and found to be a possi ble method for evaluating the M nemurus diet, as a superior ratio i ndicates superior production.